Influence of row spacing and of johnson grass competition on the crop yield of late soybean - Puricelli, Eduardo C. (Pesquisa Agropecuaria Brasileira, 1993)
In order to evaluate the effect of soybean row spacing on crop yield and johnsongrass (Sorghum halepense (L.) Pers.) biomass a study was conducted during 1988/89, 1989/90, and 1990/91. Soybean was drilled at constant density at 0.35 m and 0.70 m between rows in presence of different densities of johnsongrass. Free-weed plots were established. At harvest, crops yield and total weed biomass were determined. Correlations between weed density at 20-40 days after drilling and crop yield and weed biomass were done and slopes were statistically compared. Rainfalls in every year of the study were recorded. With unfavorable hydric conditions soybean drilled at 0.35 m seems to compete better with the crop than when seeded at 0.70 m. In more favourable environments, row spacing did not affect yields and weed biomass crop spatial arrangement did not alter weed-free soybean yields in any year of the study.